REKAYASA PERANGKAT LUNAK PENGADAAN BARANG DAN JASA DENGAN METODE E-PROCUREMENT PADA PT. INDORAMA - Andi Usri; Waliadi Gunawan (Jurnal Ilmiah Sains dan Teknologi, 2020)
PT. Indorama Polypet Indonesia is a polyester producer. In doing one production per day, it produces 500,000 tons per year. Therefore raw material or material factors are very important to support the production activities. The process of procurement and supervision of raw materials or materials is an activity to meet the needs of raw materials or materials and oversee the use of materials. PT. Indorama Polypet Indonesia has not used information technology equipment for the procurement and supervision of raw materials or materials. For the process of procuring raw materials or materials that are running still using telephone and fax, there is no system that integrates between the company and the supplier. While the process of monitoring raw materials or materials is still using a file system. From the existing problems the researchers designed an application to solve the problem of the procurement process and the supervision of raw materials or materials by building an e-procurement system. The e-procurement system was developed using the PHP programming language with Mysql as the database. It is expected that with this e-procurement system the process of procuring raw materials or materials will become more effective and efficient, because the e-procurement system integrates companies and suppliers so that it will facilitate the process of procuring raw materials or materials. As for the process of controlling raw materials or materials, e-procurement is expected to be able to supervise the use of raw materials or company materials, so that the supply of raw materials or company materials is maintained.